The Search for Oral Narratives of the Chinese Community in Semaran - G.M. Adhyanggono (Journal of Language and Literature, 2014)
Oral narratives are considered for their being out-dated, excessively glorifying and exposing the romantic past and therefore useless. Yet, it is almost forgotten that in connection with the sustainability of Indonesia as a nation there are many basic things needs preserving and developing. One of them is about the national consensus on racial and ethnical heterogeneity. The study on the Chinese community in Pecinan (Chinatown) that was conducted several years ago interestingly resulted in some facts about Chinese culture that had been silenced during the New Order regime. Regarding the fact, it is quite interesting to find out oral narratives in the community. This article is concerned with the existence of oral narratives and how they are appreciated. Keywords: oral narratives, ethnicity, race, cultural diffusion, pluralism